Pola Komunikasi Kelompok di Kalangan Lansia pada Perkumpulan Ismoyo di Desa Gogor Kecamatan Wiyung Kelurahan Jajar Tunggal Surabaya - Louisita, Hana Meidi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
This research was conducted with the background of an active group in which the group is managed whole by the Elderly. Where we all know that the elderly will naturally experience aging as well as diminish in motor power and also reminders. This does not diminish or limit the elderly to continue positive activities and interact regularly with others in the group. In the elderly group of ismoyo located in Gogor Village, Jajartunggal sub-district, Wiyung sub district, Surabaya has been established in 2007 which has active activities such as diabetes gymnastics, race activities, karawitan activities, recreational activities, mass treatment and elderly healthy way. By having existence for 10 years and also existence of 6 active activities conducted by elderly group ismoyo hence this research aim to find out whether there is group dynamics at group of ismoyo elderly.This research uses qualitative research where the object of research taken is group dynamics and group of elderly ismoyo is object of research. The data collection techniques that researchers use are field observations, interviews, documents and literature study. Data processing techniques that researchers use include data examination, data classification and data preparation. Besides, as for the 6 key informants who have conducted in-depth interviews along with the researchers, it is related to the necessary accurate data support needed during the research process took place.So the results of this study is the group of elderly ismoyo is dynamic. This is evidenced by the absence of members or individuals who are dominant in the elderly group ismoyo. With the existence of many activities or activities that exist in the elderly group ismoyo opens opportunities for other members to lead in accordance with the ability possessed by each individual.Key words : Elderly groups, group dynamics, group communication